International journal for crime, justice and social democracy - Queensland University of Technology. Crime and Justice Research Centre (Crime and Justice Research Centre, School of Justice, Faculty of Law, Queensland University of Technology, 2013)
"The International Journal for Crime, Justice and Social Democracy is an open access, blind peer reviewed journal that publishes critical research about challenges confronting criminal justice systems around the world."--Journal homepage.
Keywords: Crime : Periodicals; Criminal justice, Administration of : Periodicals; Socialism : Periodicals; Crime; Criminal justice, Administration of; Socialism; Australian